Pemanfaatan Aplikasi Powtoon Sebagai Sumber Belajar Speaking - Tities Hijratur Rahmah; Enis Fitriani; Adi Adi (IKIP Budi Utomo Malang, 2022)
Some students have difficulty in speaking English, and this happens because of various problems. One of the problems is vocabulary and pronunciation. Based on the problems stated, this study aims to explain the use of the Powtoon application as one of the learning resources needed by students. Powtoon is one of alternative application learning speaking for students now days. Powtoon application can improve student’s speaking ability because Powtoon application is a cartoon learning video that very interesting.